Implementation of Multicultural Values in the Social Interactions of Santri Who Have Different Ethnic Criteria - Nurulita, Dwita; Ma’sum Luthfilah, Mohamad; Susilo, Suko (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Education gives color to people's lives and has various functions, not only present to educate the nation's life but also specifically functions as an effort to educate themselves, socially, nation states, and the world. Culture is a way of life that develops and becomes a common habit by a group of people and is passed down to generations. With the application of the value of multiculturalism, Queen Al-Falah Islamic Boarding School Ploso Mojo Kediri instills a person who upholds the value of unity and unity against the differences that exist in the Islamic Boarding School. This study employs a qualitative methodology using descriptive analysis as the field research approach. methods for gathering data that include observation, documentation, and interviews. A flow model that incorporates data reduction, data display, and conclusion drawing is used in the data analysis process. The results of the study, namely, the implementation of the value of multiculturalism in the social interaction of students in different tribal criteria at the Queen Al-Falah Islamic Boarding School Ploso Mojo Kediri, was carried out by the management and all students of the Islamic Boarding School with humanist and tolerance values towards fellow students who have cultural and language differences and uphold a sense of nationalism.